Evaluating the Effect of Low-Level Laser Therapy as an Adjunct to Non-Surgical Periodontal Therapy on Salivary Interleukin-1ß Levels in Chronic Periodontitis - Nitesh Kumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigates the impact of low-level laser therapy (LLLT) as an adjunct to non-surgical periodontal therapy (NSPT) on salivary interleukin-1ß (IL-1ß) levels in patients with chronic periodontitis. Conducted as a randomized controlled trial with 60 participants, the study divided them into two groups: one receiving NSPT alone and the other receiving NSPT with LLLT. Salivary IL-1ß levels were measured using enzyme-linked immunosorbent assay (ELISA) at baseline, immediately after treatment, and at 1, 3, and 6 months post-treatment. The results demonstrated that the addition of LLLT significantly reduced IL-1ß levels compared to NSPT alone, suggesting that LLLT is a beneficial adjunctive therapy in managing chronic periodontitis. Chronic periodontitis, an inflammatory disease leading to the destruction of tooth-supporting structures, is traditionally managed with NSPT, primarily through scaling and root planing (SRP). LLLT, known for its anti-inflammatory and biostimulatory effects, has emerged as a promising adjunctive treatment. This study aims to evaluate the effectiveness of LLLT in reducing salivary IL-1ß levels, a key pro-inflammatory cytokine in periodontal disease. The trial included 60 patients aged 30-60 years with chronic periodontitis, randomly assigned to either NSPT alone (control) or NSPT with adjunctive LLLT (test). Participants with recent periodontal treatment, anti-inflammatory medication use, smoking habits, or pregnancy were excluded. All participants underwent NSPT, with the test group additionally receiving LLLT using a diode laser (810 nm, 0.5 W, 4 J/cm², 60 seconds per site). Salivary samples collected at baseline, immediately after treatment, and at 1, 3, and 6 months were analyzed using ELISA and repeated measures ANOVA. Baseline characteristics were comparable between groups, and while both groups exhibited a reduction in IL-1ß levels post-treatment, the NSPT + LLLT group showed a significantly greater reduction at all follow-up intervals (p < 0.05). These findings indicate that adding LLLT to NSPT significantly enhances the reduction of salivary IL-1ß levels in patients with chronic periodontitis, highlighting LLLT's anti-inflammatory and biostimulatory effects and its potential as a promising adjunctive therapy for managing chronic periodontitis.